A randomized controlled trial to assess the efficacy of standardized tai chi in prefrail older adults with immunosenescence: design and protocol - Wen Zhong; Wei Huang; Hua Deng; Shuang Qiu; Qiyue Yang; Huanan Jia (BMC Complementary Medicine and Therapies)
Abstract Background Frailty is a common geriatric syndrome worldwide, and its early identification and intervention have important clinical significance. Resistance training has been recommended as an efficient means to combat loss of muscle strength and mass; however, it is often not a prioritized option for older adults. Tai chi is a well-known traditional Chinese exercise that has a beneficial impact on physical performance, balance ability, metabolism, and immune function. Aims With the newly emerged concept of muscle-immune homeostasis, this study focused on determining the efficacy of tai chi prefrail older adults who develop immunosenescence. Furthermore, the proper timing of the exercise regimen for maximizing the therapeutic effect of tai chi has also been explored. Methods This 12-week, multicenter, randomized controlled trial (RCT) was conducted with participants between 60 and 75 years of age. A total of 144 prefrail participants were included in this study and were randomized (1:1:1:1) to four groups: (1) a control group with only health education, (2) a morning tai chi group, (3) a morning resistance training group, and (4) an afternoon tai chi group. The primary endpoints included physical performance, frailty index scores, muscle strength, and mass, and the secondary endpoints were the sarcopenia quality of life score, Berg balance scale score, bioenergetic anti-stress index (BASI), and immune risk profile (IRP). The data were analyzed according to the intention-to-treat protocol. Discussion The results of this investigation aided in determining whether tai chi effectively reversed the prefrail state of older adults and ameliorated biomarkers of immunosenescence. Furthermore, proper exercise timing was also determined to maximize the efficacy of physical training. Trial registration Chinese Clinical Trial Registry; registration number: ChiCTR2200065815; prospectively registered on November 16th, 2022.